Delineation of Sedimentary Subbasin and Subsurface Interpretation East Java Basin in the Madura Strait and Surrounding Area Based on Gravity Data Analysis - Imam Setiadi; Budi Setyanta; Tumpal Bernhard Nainggolan; Joni Widodo (Marine Geological Institute of Indonesia, 2019)
East Java basin is a very large sedimentary basin and has been proven produce hydrocarbons, this basin consists of several different sub-basins, one of the sub-basin is in the Madura Strait and surrounding areas. Gravity is one of the geophysical methods that can be used to determine geological subsurface configurations and delineate sedimentary sub-basin based on density parameter. The purposes of this study are to delineate sedimentary sub-basins, estimate the thickness of sedimentary rock, interpret subsurface geological model and identify geological structures in the Madura Strait and surrounding areas. Data analysis which used in this paper are spectral analysis, spectral decomposition filter and 2D forward modeling. The results of the spectral analysis show that the thickness of sedimentary rock is about 3.15 Km. Spectral decomposition is performed at four different wave numbers cut off, namely (0.36, 0.18, 0.07 and 0.04), each showing anomaly patterns at depth (1 Km, 2 Km, 3 Km and 4 Km). The sub-basins that can be delineated from the gravity data analysis are 10 sedimentary sub-basins, while the structural patterns identified are basement high, graben and fault. 2D modeling results indicate that the basement is a continental crust with a mass density value of 2.7 gr/cc. Sedimentary rock from modeling result consecutively from the bottom to up, the first is Paleogene sedimentary rock with mass density value of 2.4 gr/cc and above this layer is Neogene sedimentary rocks with mass density values of 2.25 gr/cc. The results of the subsurface geological modeling analysis show that based on the graben pattern and the basement high of the East Java basin in the Madura Strait and surrounding areas there are many structural patterns that support the development of petroleum systems like at the western part of the East Java basin that have already produced hydrocarbon.Keywords : Gravity, spectral analysis, spectral decomposition filter, 2D Modeling, East java basin Cekungan Jawa Timur merupakan cekungan sedimen yang sangat besar dan telah terbukti memiliki kandungan minyak dan gas bumi. Cekungan ini terdiri atas beberapa sub-cekungan yang berbeda-beda, salah satunya adalah sub-cekungan yang ada pada wilayah selat Madura dan sekitarnya. Gayaberat merupakan salah satu metoda geofisika yang dapat digunakan untuk mengetahui konfigurasi bawah permukaan serta mendelineasi sub-cekungan sedimen berdasarkan parameter rapat massa (densitas). Tujuan dari penelitian ini adalah untuk mendelineasi sub-cekungan sedimen, memperkirakan ketebalan sedimen, menginterpretasi geologi bawah permukaan serta mengidentifikasi struktur yang ada pada wilayah selat madura dan sekitarnya. Analisis data yang digunakan yaitu analisis spektral, filter spektral dekomposisi serta pemodelan maju (forward modeling) 2D. Hasil analisis spektral menunjukaan bahwa tebal batuan sedimen rata-rata adalah sekitar 3.15 Km. Spektral dekomposisi dilakukan pada empat bilangan gelombang cuttoff yang berbeda beda yaitu (0.36, 0.18, 0.07 dan 0.04) yang masing-masing menunjukkan pola anomali pada kedalaman (1 Km, 2 Km, 3 Km dan 4 Km). Sub-cekungan yang dapat didelineasi dari analisis data gayaberat ini adalah sebanyak 10 sub-cekungan sedimen, sedangkan pola struktur yang teridentifikasi yaitu berupa tinggian, graben dan patahan. Hasil pemodelan 2D menunjukkan bahwa batuan dasar adalah berupa kerak kontinen dengan nilai rapat massa 2.7 gr/cc. Batuan sedimen hasil pemodelan secara berturut turut dari bawah ke atas yang pertama yaitu batuan sedimen yang berumur Paleogen dengan nilai rapat massa 2.4 gr/cc dan di atasnya adalah batuan sedimen berumur Neogen yang mempunyai nilai rapat massa 2.25 gr/cc. Hasil analisis model bawah permukaan menunjukkan bahwa berdasarkan pola graben dan tinggian cekungan Jawa Timur segmen selat Madura dan sekitarnya cukup banyak terdapat pola struktur yang mendukung berkembangnya petroleum system seperti pada wilayah sebelah barat cekungan Jawa Timur yang sudah berproduksi hidrokarbon.Kata Kunci : Gayaberat, spektral analisis, filter spektral dekomposisi, pemodelan 2D, Cekungan Jawa Timur